Handbook of inaesthetics - Badiou, Alain; Toscano, Alberto (Stanford, Calif. : Stanford University Press, 2005)
- - Art and philosophy ##- - What is a poem?, Or, philosophy and poetry at the point of the unnamable ##- - A French philosopher responds to a Polish poet ##- - A philosophical task: to be contemporaries of Pessoa ##- - A poetic dialectic: Labîd ben Rabi'a and Mallarmeʹ ##- - Dance as a metaphor for thought ##- - Theses on theater ##- - The false movements of cinema ##- - Being, existence, thought: prose and concept ##- - Philosophy of the faun.
Includes bibliographical references (p. 142-148).
boek